Connecting With the Hyper(dis)connected Audience: University Communication Attributes and Student Attitudes - Samar Ben Romdhane; Mokhtar Elareshi; Mohammed Habes; Amal Hassan Alhazmi; Razaz Waheeb Attar (SAGE Open)
Today’s empowered and hyper(dis)connected generation expects from higher education institutions (HEIs) communication strategies that align with their interests, making communication strategies crucial for their ongoing experience at the University. Once students are recruited, the factors they consider important when choosing a university may continue to shape their attitudes toward their institution. Universities continue to innovate in their communication strategies to face intense competition not only in attracting but also in retaining and engaging students. This study investigates the salience of university communication-related attributes and their relationship with student attitudes. Three communication-related attributes (opinion leader recommendations and online and offline messages and four students’ attitudes (institutional commitment, degree commitment, social integration, and academic integration) were measured through an online survey. The study offers critical insights to align the attributes promoted during students recruitment with the current experiences at the University.